Just Checking It Out? Motivations for and Behavioral Associations With Visiting “Slutpages” in the United States and Australia - Clancy, Elizabeth M.; Maas, Megan K.; March, Evita; Howard, Dominika; Klettke, Bianca (Frontiers in Psychology, 2021)
“Slutpages” are a pernicious form of online image-based evaluative voyeurism (OIBEV), whereby (sexualized) images of women are posted on webpages for (predominantly) male groups to rate and comment. Despite media and public concern, OIBEV sites have garnered limited empirical study. This paper presents the first analysis of OIBEV site visitation motivations across United States and Australian samples. Participants comprised a convenience sample of 1148 young adults aged 18 to 29 years (M = 22.54, SD = 2.50); 53.0% women, 47.0% men; 54% residing in the U.S. and 46% in Australia. Respondents completed an online questionnaire. Overall, 23% of United States and 16% of Australian respondents had visited OIBEV sites. OIBEV site visitation was uniquely associated with gender and country (with men and United States being more likely to visit OIBEV sites), requesting and disseminating sexts and having one’s own image shared. Cyberbullying perpetration was associated with reduced odds of OIBEV site visitation. Motivations differed by gender, with men (80%) being most likely to visit sites to “check them out” while women were equally likely to check it out (41%) or to see if they were depicted (36%). For men, unique predictors of OIBEV site visitation were having requested, disseminated and received disseminated sexts, lower levels of anxiety and reduced likelihood of cyberbullying perpetration. For women, OIBEV site visitation was uniquely associated with being a United States resident, sext dissemination victimization, receipt of disseminated sexts, higher levels of anxiety but reduced stress. Our findings confirm that OIBEV sites represent a highly gendered form of online image-based sexual abuse, and may have important mental health implications, given the associations with increased anxiety. Our results support the need for “slutpage” education for adolescents and young adults to address social and peer norms that encourage and support non-consensual use of intimate images.